Molecular basis of alpha-tocopherol control of smooth muscle cell proliferation - KARTAL ÖZER, NESRİN (WILEY, 1998)
Rat and human vascular smooth muscle cell proliferation is specifically sensitive to alpha-tocopherol, but not beta-tocopherol. The former, but not the latter, is capable of limiting proliferation and inhibiting protein kinase C activity in a dose-dependent manner. The phenomenon occurs at concentrations in the range 10-50 mu M. beta-tocopherol addition together with alpha-tocopherol, prevents both cell growth and protein kinase C inhibition. alpha-tocopherol increases de novo synthesis of protein kinase C molecules. The enzyme specific activity, however, is diminished, due to a decreased phosphorylation of protein kinase C, occurring in the presence of alpha-tocopherol. Experiments with protein kinase C isoform-specific inhibitors and precipitating antibodies show that the only isoform affected by alpha-tocopherol is protein kinase C-alpha. The effect of alpha-tocopherol is prevented by okadaic acid indicating a phosphatase of the PP2A type as responsible for protein kinase C-alpha dephosphorylation produced in the presence of alpha-tocopherol. At a gene level alpha-tocopherol but not beta-tocopherol induces a transient activation of alpha-tropomyosin gene transcription and protein expression. It is proposed that, by inhibiting protein kinase C activity via an activation of a phosphatase PP2A, alpha-tocopherol controls smooth muscle cell proliferation through changes in gene expression.
Keywords: alpha-tocopherol; vitamin E; protein kinase C; vascular smooth muscle cell; cell proliferation; protein phosphatase; oxidative stress